A Comparison of Acellular Dermal Matrices in Abdominal Wall Reconstruction. Issue 4 (April 2019) - Maxwell, Daniel W.; Hart, Alexandra M.; Keifer, Orion P.; Halani, Sameer H.; Losken, Albert
Abstract : Background: There is a growing literature of evidence that the use of acellular dermal matrices (ADMs) in abdominal wall reconstruction (AWR) for high-risk patients provides superior complication profiles when compared with standard synthetic mesh. Here we compare Fortiva, Strattice, and Alloderm ADMs in AWR. Methods: In a prospectively maintained database, all patients undergoing AWR between January 2003 and November 2016 were reviewed. Hernia recurrence and surgical site occurrence (SSO) were our primary and secondary endpoints. Kaplan-Meier survival curves and logistic regression models were used to evaluate risks for hernia recurrence and SSO. Results: A total of 229 patients underwent AWR with 1 of 3 ADMs. Median follow-up time was 20.9 months (1–60 months). Cumulative recurrence rates for each mesh were 6.9%, 11.2%, and 22.0% ( P = 0.04), for Fortiva, Strattice, and Alloderm groups. Surgical site occurrence for each mesh was 56.9%, 49.0%, and 49.2%, respectively. Seroma was significantly lower in the Fortiva group (1.4%; P = 0.02). Independent risk factors hernia recurrence included body mass index of 30 kg/m 2 or higher and hypertension. Adjusted risk factors included oncologic resection for hernia recurrence (odds ratio, 5.3; confidence interval, 1.1–97.7; P = 0.11) and a wound class of contaminated or dirty/infected for SSO (odds ratio, 3.6; confidence interval, 1.0–16.6; P = 0.07). Conclusions: Acellular dermal matrices provide a durable repair with low overall rate of recurrence and complications in AWR. The recurrence and complication profiles differ between brands. With proper patient selection and consideration, ADMs can be used confidently for a variety of indications and wound classifications.